Diagnostic dilemmas in Epstein-Barr virus hepatitis mimicking autoimmune hepatitis: A case report - Ramachandran, Krithiga (J Family Med Prim Care, 2020)
We report a case of 55-year-old female with chief complaints of fever and deranged liver function tests, diagnosed as autoimmune hepatitis (AIH) and under immunosuppressive therapy for two years. Following the failure in clinical improvement, she was started on anti-tubercular therapy (ATT). While investigating the underlying etiology, virological markers for Hepatitis A to E were found to be negative with plasma Epstein-Barr virus (EBV) viral load of 5 log(10) copies/ml. Additional investigation of the liver biopsy showed Hodgkin's lymphoma (HL). The patient was initiated on chemotherapy but eventually succumbed to the illness. This case report underlines the dilemma in the initial diagnosis of AIH and the importance of considering hepatic involvement of EBV as one of the differential diagnosis among clinically suspected AIH cases not responding to immunosuppressive medications.